Liesl & Po - Oliver, Lauren, 1962- (Harper, 2012)
Relegated to her attic bedroom, Liesl is all alone until she meets a ghost named Po, who comes from the Other Side. While they get to know one another, Will, an alchemist's apprentice, mixes up a box containing the most powerful magic in the world with another containing something far less extraordinary. This mix-up launches all three on a harrowing journey that will change their lives forever.